2022
DOI: 10.18176/jiaci.0641
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dupilumab in 543 Adult Patients With Moderate-to-Severe Atopic Dermatitis: A Multicenter, Retrospective Study

Abstract: Background: Dupilumab has been demonstrated to be an effective treatment for patients with moderate-to-severe atopic dermatitis (AD) in clinical trials. However, evidence of real-world experience with dupilumab in a broader population is limited to date. Methods: Adult patients with moderate-to-severe AD, defined as an Eczema Area Severity Index (EASI) score of 24 or higher, treated with dupilumab at ten Italian academic centers, were included in the study. Physician-reported outcome measures (EASI), patient-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 41 publications
8
40
0
1
Order By: Relevance
“… 8 The EASI-50 (85.7%–98.1%) and EASI-75 (60.6%–81.5%) response rates at week 16 with concomitant medications in the real clinical practice were reported to be higher in recently published real-world studies than in our study. 11 24 25 26 In these real-world studies, dupilumab was administered biweekly, which may explain why the clinical outcomes were better in those studies than in our study.…”
Section: Discussionmentioning
confidence: 67%
“… 8 The EASI-50 (85.7%–98.1%) and EASI-75 (60.6%–81.5%) response rates at week 16 with concomitant medications in the real clinical practice were reported to be higher in recently published real-world studies than in our study. 11 24 25 26 In these real-world studies, dupilumab was administered biweekly, which may explain why the clinical outcomes were better in those studies than in our study.…”
Section: Discussionmentioning
confidence: 67%
“…Real-world evidence of the effectiveness and safety of dupilumab for atopic dermatitis Accumulating real-world evidence has ensured the effectiveness and tolerable safety of dupilumab both in the short term and in the long term. The articles searched in PubMed and Google Scholar are shown in Table 1 (Ariëns et al, 2020, Ariëns et al, 2021, Faiz et al, 2019, Fargnoli et al, 2020, Fargnoli et al, 2019, Jang et al, 2020, Jo et al, 2020a, Kreeshan et al, 2021, Matsutani et al, 2020, Nettis et al, 2020b, Nettis et al, 2020c, Olesen et al, 2019, Patruno et al, 2021a, Patruno et al, 2021b, Quint et al, 2020, Ribero et al, 2020, Sears et al, 2020, Tauber et al, 2019, Uchida et al, 2021, Uchida et al, 2019. Patruno et al reported the effectiveness and safety of dupilumab in elderly patients with AD in real life (Patruno et al, 2021a, Patruno et al, 2021b.…”
Section: Effectiveness and Safety Of Dupilumab For Atopic Dermatitis In The Real Worldmentioning
confidence: 99%
“…Accumulating real-world evidence has ensured the effectiveness and tolerable safety of dupilumab both in the short term and in the long term. The articles searched in PubMed and Google Scholar are shown in Table 1 ( Ariëns et al., 2021 , 2020 ; Armario-Hita et al., 2019 ; Faiz et al., 2019 ; Fargnoli et al, 2020 , 2019 ; Ferrucci et al., 2020 ; Jang et al., 2020 ; Jo et al., 2020a , 2020b ; Kim et al., 2020 ; Kreeshan et al., 2021 ; Matsutani et al., 2020 ; Nettis et al., 2020b , 2020c ; Olesen et al., 2019 ; Patruno et al., 2021a , 2021b ; Quint et al., 2020 ; Ribero et al., 2020 ; Sears et al., 2021 ; Tauber et al., 2019 ; Tavecchio et al., 2020 ; Uchida et al., 2021 , 2019 ; Wang et al., 2020 ; Yamauchi et al., 2021 ). Patruno et al.…”
Section: Effectiveness and Safety Of Dupilumab For Ad In The Real Worldmentioning
confidence: 99%
“…The combination of Dennie-Morgan fold and POH is highly suspicious for atopic dermatitis [2]. Atopic dermatitis is probably the most common dermatosis associated with POH [3]. Several medical drugs may cause POH, such as prostaglandins or imatinib [4,5].…”
Section: Introductionmentioning
confidence: 99%